2017
DOI: 10.12659/msm.904683
|View full text |Cite
|
Sign up to set email alerts
|

Folic Acid-Targeted Etoposide Cubosomes for Theranostic Application of Cancer Cell Imaging and Therapy

Abstract: BackgroundThe aim of this study was to develop a novel Poloxamer-based drug delivery system featuring a tumor-targeting folate moiety, which was expected to provide better targeting properties and therapeutic effects compared with the traditional cubosomes (Cubs).Material/MethodsBoth folate-modified Cubs containing etoposide (ETP-Cubs-FA) and normal cubic nanoparticles loaded with etoposide (ETP-Cubs) were prepared through the fragmentation of bulk gels under the homogenization condition of 1500 bar, and a mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“… 23 The formulated thymoquinone loaded cubosomes particle size was of nanometric size similar to those reported in literature. 32 In Tian et al study, etoposide loaded-cubosomes had particle sizes of 173.6 ± 1.60 nm with 0.174 PDI value; the consistent low PDI in various studies demonstrated the ability of cubosomes dispersion to maintain homogeneity, yet the observed particle size difference is clarified by the modified formulation and process parameters. This is further evident by Swarnakar et al study which highlighted the effect of the formulation factors as well as the process parameters as the surfactant nature and its concentration, drug loading as well as the sonication time on the cubosomes particle size and PDI.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“… 23 The formulated thymoquinone loaded cubosomes particle size was of nanometric size similar to those reported in literature. 32 In Tian et al study, etoposide loaded-cubosomes had particle sizes of 173.6 ± 1.60 nm with 0.174 PDI value; the consistent low PDI in various studies demonstrated the ability of cubosomes dispersion to maintain homogeneity, yet the observed particle size difference is clarified by the modified formulation and process parameters. This is further evident by Swarnakar et al study which highlighted the effect of the formulation factors as well as the process parameters as the surfactant nature and its concentration, drug loading as well as the sonication time on the cubosomes particle size and PDI.…”
Section: Discussionmentioning
confidence: 91%
“…The amount of thymoquinone in the recovery chamber was quantified by high pressure liquid chromatography (HPLC). The entrapment efficiency of thymoquinone was calculated as follows: 32 %EE ¼ ðTotal weight of TQ added À Weight of unentrapped TQÞ=Total weight of TQÞ X 100…”
Section: Entrapment Efficiency Of Thymoquinone In Lcnpsmentioning
confidence: 99%
“…Targeting therapy has become the new therapeutic approach for cancer treatment. This involves delivery of the anticancer drugs at the specific site without any cytotoxic effects on other tissues or organs 43 , where the effects of cancer may be reduced/reversed. The concept and development of lipid nanovehicles have been originated in 1970s, which are in the mould of continuous modification until today.…”
Section: Discussionmentioning
confidence: 99%
“…carriers. 54,55 Another approach involves common modifications with specific ligands to protein receptors expressed on the surface of the cancer cells, typically folic acid ligands 56 or the tumor-homing and tumor-penetrating cyclic iRGD peptide, also due to its ability to increases the tumor vascular permeability. 57,58 Of course, the anti-cancer efficacy of the GMO-AT101 formulation requires further investigation in the GBM model in vivo.…”
Section: Encapsulated At101 Exhibits Stronger Cytotoxic Effects and Mmentioning
confidence: 99%